A Ferris Wheel Accident at a Movable Amusement Park. Issue 3 (19th December 2016) - Cho, Young‐Jin; Ji, Hong‐Keun; Moon, Byung‐Sun; Park, Ha‐Sun; Goh, Jae‐Mo; Park, Nam‐Kyu; Choi, Don‐Mook
Abstract: This study presented a Ferris wheel accident case. A Ferris wheel is composed of many parts, and the outmost ring of it is assembled using a lock pin. This accident occurred because the lock pin caught the door of a gondola and the gondola overturned. Five of the seven passengers in the gondola fell to the ground, along with the gondola's viewing window. The investigation revealed that the gondola became stuck when its door was caught by a lock pin at the Ferris wheel's three o'clock position. The contact between the door and the lock pin was due to a structural problem: There was not enough space allotted between the door and the lock pin. Therefore, if a passenger pushed on the gondola's door, the potential existed for contact between the door and the lock pin.